Pendampingan Membuat Media Pembelajaran Digital dengan Memanfaatkan Artificial Intelligence Bagi Guru Sekolah Menengah Pertama - Sundari; Dehen Erang; Sumarnie; Agus Saputra; Tanti Girsang (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
The purpose of this service is to assist junior high school teachers in creating digital learning media based on artificial intelligence and to enable them to be implemented independently in the teaching and learning process. This activity was carried out from September to November 2023 at SMP Negeri 16 Palangka Raya. The stages of implementing this service activity are: coordination with partners, Training Implementation, and Mentoring Implementation. This mentoring activity has succeeded in achieving the main goal, which is to improve the competence of SMP Negeri 16 Palangka Raya teachers in creating Digital Learning Media based on Artificial Intelligence (AI). Teachers who previously only had basic computer and internet skills are now able to utilize various AI-based applications such as Google Workspace, Canva, and Microsoft Office 365 to create teaching modules and teaching materials that are interactive, engaging, and relevant to the needs of students in the digital era. This activity also succeeded in increasing the confidence of teachers in adopting new technology into the learning process. From the results of this activity, some of the challenges faced, such as the difference in the level of technology mastery among teachers, can be solved through direct guidance and intensive mentoring. Teachers feel helped by the existence of training modules, technical instructions, and support from students and resource persons. This shows that well-designed training, supported by adequate facilities and infrastructure, is able to have a positive impact on the development of educators' competencies.